2003
DOI: 10.1088/0954-3899/29/5/316
|View full text |Cite
|
Sign up to set email alerts
|

Current views on impulsive and gradual solar energetic particle events

Abstract: Solar energetic particles (SEPs) are one manifestation of violent energy releases on the Sun. The study of their acceleration and propagation reveals information about basic plasma-physical processes, such as reconnection, shock acceleration and wave-particle interaction, in astrophysical objects, such as stars, magnetospheres or the diluted plasma of the interstellar or interplanetary medium. This paper introduces the current classification scheme for solar energetic particle events, its relation to the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 142 publications
3
91
0
6
Order By: Relevance
“…Nonetheless, this ''two class'' picture has proved to be an oversimplification and does not match the diversity and wealth of the observed SEP event properties (Cane et al 2010). Furthermore, observations have indicated that there is a third category of events, the so-called hybrid or mixed events, during which both SFs and CMEdriven shocks accelerate particles that contribute to large SEP events (Kocharov & Torsti 2002;Kallenrode 2003). These hybrid or mixed events may look like gradual events but demonstrate properties of impulsive ones (Vainio et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this ''two class'' picture has proved to be an oversimplification and does not match the diversity and wealth of the observed SEP event properties (Cane et al 2010). Furthermore, observations have indicated that there is a third category of events, the so-called hybrid or mixed events, during which both SFs and CMEdriven shocks accelerate particles that contribute to large SEP events (Kocharov & Torsti 2002;Kallenrode 2003). These hybrid or mixed events may look like gradual events but demonstrate properties of impulsive ones (Vainio et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the CME-driven shock, the proton acceleration is considered to be gradual, in which energetic particles are dominant in the initial stage, and low-energy particles arise later as the shock propagates further into the solar wind [Zank et al, 2000]. However, as various conditions and mechanisms are entangled in the proton acceleration, our physical understanding of the origin and mechanism of SPEs still remains incomplete [Kallenrode, 2003;Trottet et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, observations have indicated that there are 'hybrid' or mixed event cases, where both mechanisms appear to contribute, with one accelerating mechanism operating in the flare while the other operates at the CME-driven shock (Kallenrode 2003). Such hybrid events may result from the re-acceleration of remnant flare suprathermals by shock waves (Mason et al 1999;Desai et al 2006) or from the interaction of CMEs (Gopalswamy et al 2002).…”
Section: Fig 12mentioning
confidence: 99%
“…In fact during the September 1989 event, even an astronaut behind 10 g cm 2 of material would receive a dose of 40 mSv. The annual dose limit for a radiation worker in the United States is 20 mSv (Zeitlin et al 2013;Kerr 2013). In each solar cycle several events of this intensity occur, thus, knowledge of the spectral knee energies is essential.…”
Section: Fig 12mentioning
confidence: 99%